2019
DOI: 10.1016/j.jcot.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative hematocrit on early prosthetic joint infection and deep venous thrombosis rates in primary total hip arthroplasty: A database study

Abstract: Background: Total hip arthroplasty (THA) is a very successful surgery in restoring a patient's quality of life. Infection is a devastating complication of THA. Many risks factors for infection in THA have been identified but little is known of the effect by preoperative hematocrit. Purpose: We aimed to evaluate the effect of preoperative hematocrit on early superficial site infections, deep infections, and deep organ space infections. Methods: Our study cohort included patients undergoing a THA in the ACS Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The lower hematocrit was also found to be associated with increased risk of DSSI in this study, in line with the previous reports. Willis et al [ 28 ] found the increased 2.38-fold risk of DSSI and 3.05-fold risk of organ space infection associated with preoperative lower hematocrit, but not for superficial infection, following 98,869 cases of total hip arthroplasty. Keswani et al [ 29 ] demonstrated that lower preoperative hematocrit was not only an independent risk for 30-day complications including deep wound infection, but also increased the 30-day unplanned readmission or severe adverse event by 5.24 times following revision shoulder arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower hematocrit was also found to be associated with increased risk of DSSI in this study, in line with the previous reports. Willis et al [ 28 ] found the increased 2.38-fold risk of DSSI and 3.05-fold risk of organ space infection associated with preoperative lower hematocrit, but not for superficial infection, following 98,869 cases of total hip arthroplasty. Keswani et al [ 29 ] demonstrated that lower preoperative hematocrit was not only an independent risk for 30-day complications including deep wound infection, but also increased the 30-day unplanned readmission or severe adverse event by 5.24 times following revision shoulder arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Specific at trauma, lower hematocrit may represent an acute blood loss status after fracture, also may reflect the concurrent medical condition or nutritional status. Anyhow, it is prudent to appropriately delay surgery, or consider addition of an iron supplement or erythropoietin to restore blood stores prior to surgery [ 28 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have identified that preoperative anemia is associated with an increased rate of complications after total joint arthroplasty. 24 25 26 27 28 29 Viola et al 28 identified an association between preoperative anemia, defined by hemoglobin <12 g/dL for women and <13 g/dL for men, and increased rates of postoperative complications and mortality after total knee arthroplasty and total hip arthroplasty. Similarly, Grosso et al 25 identified preoperative anemia, defined by hematocrit <36%, as a notable risk factor for mortality, renal complications, respiratory complications, sepsis, wound infection, and UTI after THA.…”
Section: Discussionmentioning
confidence: 99%